One-step engineered self-assembly Co3O4 nanoparticles to nanocubes for supercapacitors. (16th February 2018) - Nagajyothi, P C; Pandurangan, M; Sreekanth, T V M; Shim, Jaesool
Abstract: Tricobalt tetraoxide or cobalt oxide (Co3 O4 ) nanocubes (NCs) were synthesized from the self-assemblies of Co3 O4 nanoparticles (NPs) via a simple one-step hydrothermal method. X-ray diffraction analysis confirmed the cubic crystal structure of Co3 O4 NCs. The surface properties were investigated by x-ray photoelectron spectroscopy, which suggests the co-existence of Co in +2 and +3 states. The self-assemblies of aggregation of NPs to NCs were inspected using scanning electron microscopy, which is supported by transmission electron microscopy. The electrochemical properties of Co3 O4 NCs were carried out by cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) curves and impedance analysis. The areal capacitance of 3.04 mF cm −2 was obtained at current density of 10 μ A cm −2 . The Co3 O4 NCs electrode exhibits good long-cyclic stability with 92.1% capacitance retention over 3000 cycles. The CV, GCD and impedance curves of Co3 O4 NCs were recorded after cyclic test, which are similar to the curves recorded before the test. Therefore, the Co3 O4 NCs serves good candidate as positive electrode materials for asymmetric supercapacitors.